Kajian Etnografi Tradisi Uang panai Dalam Perspektif Akuntansi Hutang Piutang - Hidayat, Muhammad Fery; Wellem, Karmila Alamsyah (CV. ITTC INDONESIA, 2025)
This study arises from the phenomenon of the uang panai tradition among the Bugis community, which is seen on one hand as a symbol of siri’ (family honor) for the bride’s family, yet on the other hand imposes an economic burden on the groom’s side. The study aims to analyze the practice of uang panai from a debt-accounting perspective, using the frameworks of PSAK 1 (2023) and PSAK 50 (2014). The research employed a qualitative approach with an ethnographic design, using participant observation, in-depth interviews, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2018). The findings indicate that the groom’s side perceives uang panai as a liability to be fulfilled, while the bride’s side sees it as a receivable and a symbol of family honor. The practice reflects the recording and recognition of obligations and claims akin to formal accounting, albeit within a cultural context. The study also identifies the risk of default, which may result in delayed or canceled marriages, or even silariang (elopement). Thus, the uang panai tradition can be understood as a form of cultural accounting practice that bridges symbolic values with the economic realities of the Bugis community.